Genome sequencing among children with medical complexity: What constitutes value from parents' perspective?. Issue 2 (21st October 2021) - Lee, Whiwon; Luca, Stephanie; Costain, Gregory; Snell, Meaghan; Marano, Maria; Curtis, Meredith; Dunsmore, Kourtney; Veenma, Danielle; Walker, Susan; Cohn, Ronald D.; Marshall, Christian R.; Cohen, Eyal; et al.
Abstract: Genome sequencing (GS) has demonstrated high diagnostic yield in pediatric patients with complex, clinically heterogeneous presentations. Emerging evidence shows generally favorable experiences for patients and families receiving GS. As a result, implementation of GS in pediatrics is gaining momentum. To inform implementation, we conducted a qualitative study to explore the personal utility of GS for parents of children with medical complexity (CMC). GS was performed at an academic tertiary‐care center for CMC for whom a genetic etiology was suspected. Following the return of GS results, semi‐structured interviews were conducted with 14 parents about their child's diagnostic journey. Of the children whose parents were interviewed, six children received a diagnosis, two received a possible diagnosis, and six did not receive a diagnosis. A predominantly deductive thematic analysis approach to the interview data was used by applying Kohler's personal utility framework to understand affective, cognitive, behavioral and social impacts of GS. Both the diagnosed and undiagnosed groups experienced enhanced emotion‐focused coping (affective). The diagnosed group experienced favorable utility related to knowledge of condition (cognitive) and communication with relatives (behavioral). A domain beyond Kohler's framework related to the presence or absence of GS impact on medical management was also described by parents. The deployment of GS late in the diagnostic odyssey and the limited knowledge available for the rare genetic disorders diagnosed in this cohort appeared to diminish the perceived utility of GS. As GS capabilities continue to evolve at a rapid pace and become available earlier in the diagnostic journey, it is important to consider the impact and timing of testing on parents of CMC.